REINTERPRETING CODE IS LAW IN THE AGE OF ARTIFICIAL INTELLIGENCE: TOWARD A TECHNO-LEGAL GOVERNANCE FRAMEWORK - Emi Anggreani Masjur (Penelitian dan Pengembangan Ilmu, 2026)
Digital technologies especially algorithms and AI have shifted legal normativity by embedding regulation into code and platform architectures, reshaping how behavior is governed in digital societies. This article asks whether Lawrence Lessig’s Code is Law thesis still adequately explains regulation in AI driven, platform based environments, or whether it must be reinterpreted to address rising concerns about accountability, transparency, and power asymmetries. Using a doctrinal and conceptual legal research approach, the study examines legal theory, regulatory frameworks, and scholarship on algorithmic governance and digital regulation. Through hermeneutic interpretation and comparative reasoning, it contrasts formal legal rules with code based governance and synthesizes the findings into an expanded techno legal governance framework. The analysis concludes that Code is Law remains analytically useful but is insufficient in its original form. It reframes code as a parallel yet governable regulatory force embedded within legal, ethical, and institutional structures, providing a foundation for hybrid governance in the age of AI.